Uni-REPM SCS: A Safety Maturity Model for Requirements Engineering Process - Vilela, Jéssyka; Castro, Jaelson; Martins, Luiz Eduardo (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2019)
Context: Software is an important part in safety-critical system (SCS) development since it is becoming a major source of hazards. Software has been responsible to implement innovative and complex functions and to send instructions to the hardware. Requirements-related hazards have been associated with many accidents and safety incidents. Requirements issues tend to be mitigated in companies with high processes maturity levels since they adopt good practices from software engineering in a systematic, consistent and proactive way. However, requirements engineers need systematic guidance to consider safety concerns early in the development process. Objective: This thesis investigates which safety practices/actions are suitable to be used in the Requirements Engineering process of SCS as well as to propose a safety maturity model to this area. Method: A set of empirical studies were used in this work. The data collection was done through systematic literature review and case studies. We followed the Design Science methodology to propose Uni-REPM SCS, a safety module for Unified Requirements Engineering Process Maturity Model (Uni-REPM), and the technology transfer framework to perform the safety module validation. Besides, comprehensive literature review was also conducted to provide background and support for the empirical studies. Results: The safety module has seven main processes, 14 sub-processes and 148 safety actions describing principles and practices that form the basis of safety processes maturity. Moreover, we describe its usage through a tool. We conducted a static validation with two practitioners and nine academic experts to evaluate its coverage, correctness, usefulness and applicability. Furthermore, we performed a dynamic validation with seven industry practitioners to evaluate the safety maturity level of seven industry projects. Conclusions: The validation indicates a good coverage of practices and good receptivity by the experts. Finally, the module can help companies in evaluating their current practices as well as offers a step-wise improvement strategy to reach higher maturity.